Application of three‐dimensional print in minor hepatectomy following liver partition between anterior and posterior sectors. Issue 9 (20th December 2017) - Igami, Tsuyoshi; Nakamura, Yoshihiko; Oda, Masahiro; Tanaka, Hiroshi; Nojiri, Motoi; Ebata, Tomoki; Yokoyama, Yukihiro; Sugawara, Gen; Mizuno, Takashi; Yamaguchi, Junpei; Mori, Kensaku; Nagino, Masato
Abstract : Background: Minor hepatectomy following liver partition between the right anterior and posterior sectors requires technical ingenuities. In such hepatectomy, we used three‐dimensional (3D) print; therefore, our procedure was introduced. Methods: Digital segmentation of anatomical structures from multidetector‐row computed tomography images utilized the original software 'PLUTO', which was developed by Graduate School of Information Science, Nagoya University. After changing the final segmentation data to the stereolithography files, 3D‐printed liver at 70% scale was produced. The support material was washed and mould charge was removed from 3D‐printed hepatic veins. The surface of 3D‐printed model was abraded and coated with urethane resin paint. After natural drying, 3D‐printed hepatic veins were coloured by injection of a dye. The 3D‐printed portal veins were whitish because mould charge remained. All procedures after 3D printing were performed by hand work. A 3D‐printed model of the right posterior sector and a 3D‐printed model of other parenchyma were produced, respectively. Measuring the length between the main structures on the liver surface and the planned partition line on the 3D‐printed model, land mark between the right anterior and posterior sectors on the real liver surface was produced with scale adjustment. Results: Minor hepatectomy following liver partition between the right anterior and posterior sectors was performed referring to 3D‐printed model. The planned liver partition and resection were successful. Conclusions: Application of 3D‐printed liver to minor hepatectomy following liver partition between the right anterior and posterior sectors is easy and a suitable procedure.